Analisis Kematangan dan Adopsi Teknologi AI Video dalam Transformasi Digital Multi-Sektoral 2025-2030 - Afkar, Muhammad Agha (Yayasan Kawanad, 2024)
This research analyzes the development and adoption of AI Video technology through a comprehensive approach that evaluates technological maturity levels, sectoral adoption patterns, implementation challenges, and future growth projections. The analysis reveals that AI Video technology has entered a critical transformation phase from experimental to mainstream adoption with heterogeneous maturity levels across components. Object Detection has reached mature and deployment phases with widespread adoption in commercial applications, while Video Generation remains in transition from development to testing, and Edge Computing stays predominantly in research phase despite high disruptive potential. Adoption patterns show significant asymmetry across sectors, with entertainment achieving the highest adoption (90%), followed by retail (75-80%), healthcare and education (60-65%), and government showing the lowest (40-45%). Computational Cost emerges as the primary challenge (>87.5%), followed by Ethical Issues (85%) which demonstrates a significant gap between compliance requirements and current technical capabilities. Growth projections for 2025-2030 show optimism with Ethical AI projected to grow 55%, Real-time Generation 55%, and Edge Computing 50%. Convergence with other emerging technologies creates an integrated ecosystem but increases implementation complexity. Strategic recommendations include phased implementation based on technology maturity, computational infrastructure investment, comprehensive ethical framework development, and multi-stakeholder collaboration for sustainable and responsible development.